2006
DOI: 10.1111/j.1365-2656.2006.01193.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex and testosterone effects on growth, immunity and melanin coloration of nestling Eurasian kestrels

Abstract: Summary1. Sex differences in testosterone levels and sex-biased sensitivity to testosterone are the basis of some ideas postulated to account for sex-linked environmental vulnerability during early life. However, sex variation in circulating testosterone levels has been scarcely explored and never manipulated at post-natal stages of birds in the wild. 2. We measured and experimentally increased circulating testosterone levels in nestling Eurasian kestrels Falco tinnunculus . We investigated, possible sexual di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
68
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 74 publications
6
68
1
Order By: Relevance
“…Fargallo et al 2002;Hõrak et al 1999;Saino et al 1997). Second, lower immune responses in large broods might be caused by increased sibling competition resulting in an increase in testosterone (Naguib et al 2004) and a suppressed immune function (Boonekamp et al 2008;Fargallo et al 2007;Folstad and Karter 1992; but see Roberts et al 2004). Evidence for immunosuppressive effects of testosterone, however, is still lacking for zebra finches.…”
Section: Discussionmentioning
confidence: 99%
“…Fargallo et al 2002;Hõrak et al 1999;Saino et al 1997). Second, lower immune responses in large broods might be caused by increased sibling competition resulting in an increase in testosterone (Naguib et al 2004) and a suppressed immune function (Boonekamp et al 2008;Fargallo et al 2007;Folstad and Karter 1992; but see Roberts et al 2004). Evidence for immunosuppressive effects of testosterone, however, is still lacking for zebra finches.…”
Section: Discussionmentioning
confidence: 99%
“…There is good evidence of the immunosuppressive nature of T in laboratory mammals (Grossman, 1985), and several manipulative avian studies have found a deleterious effect of elevated T on humoral immunity (Duffy et al, 2000;Peters, 2000;Casto et al, 2001;Buchanan et al, 2003;Owen-Ashley et al, 2004;Deviche and Cortez, 2005), as well as on cell-mediated immunity (Duffy et al, 2000;Casto et al, 2001;Owen-Ashley et al, 2004;Deviche and Cortez, 2005;Boughton et al, 2007;Fargallo et al, 2007). However, other studies have found no such effect on either humoral (Hasselquist et al, 1999;Roberts et al, 2007a) or cellmediated immunity (Buchanan et al, 2003;Greenman et al, 2005;Roberts et al, 2007a).…”
Section: Introductionmentioning
confidence: 85%
“…Among them, the melanocortin system also regulates a diverse array of physiological functions, including adrenocortical steroidogenesis and anti-inflammatory responses (Cone 2006, Ducrest et al 2008. Relationships among melanin-based phenotypes and immunity (e.g., Gasparini et al 2009, Jacquin et al 2011, Parejo et al 2011; but see González et al 1999;Pärn et al 2005;Fargallo et al 2007a, b), parasite infection (e.g., Fitze and Richner 2002, Chakarov et al 2008, Jacquin et al 2011, testosterone levels (Fargallo et al 2007b, Bókony et al 2008, and corticosterone levels (Pryke et al 2012) have been observed in birds, demonstrating in some cases and suggesting in others that melanic phenotypes can signal immune capacity and endocrine profiles.…”
mentioning
confidence: 99%